Adjuvant chemotherapy in biliary tract cancer patients: A systematic review and meta-analysis of randomized controlled trials. (May 2020) - Caparica, Rafael; Bruzzone, Marco; Hachem, Georges El; Ceppi, Marcello; Lambertini, Matteo; Glasberg, João; de Azambuja, Evandro; Van Laethem, Jean-Luc; Hendlisz, Alain
Graphical abstract: Abstract: Background: The role of adjuvant chemotherapy in biliary tract cancer is controversial. We performed a systematic review and meta-analysis to assess the effect of adjuvant chemotherapy in biliary tract cancer patients. Methods: A literature search was performed to identify randomized controlled trials (RCTs) comparing adjuvant chemotherapy versus observation, and a pooled analysis was conducted using the random-effect model. Results: Three RCTs ( N = 866) were included. No difference was observed between chemotherapy and observation in terms of OS (HR 0.91; 95 %CI, 0.75–1.09; p = 0.295), whereas a significant improvement in RFS was shown (HR 0.83; 95 %CI, 0.69-0.99; p = 0.040). No subgroup that benefited most from adjuvant chemotherapy was identified, although a trend was observed in N+ patients (HR 0.83; 95 %CI, 0.65–1.08; p = 0.165). Discussion: Adjuvant chemotherapy yields a significant RFS benefit in biliary tract cancer patients and should be considered for those who are able to tolerate additional treatment after surgery.